1993
DOI: 10.1111/j.1749-6632.1993.tb23036.x
|View full text |Cite
|
Sign up to set email alerts
|

Production of Amyloid β Protein from Normal Amyloid β‐Protein Precursor (βAPP) and the Mutated βAPPS Linked to Familial Alzheimer's Diseasea

Abstract: The approximately 4 kD (39-43 amino acid) polypeptide (amyloid beta protein, A beta) deposited as amyloid in Alzheimer's disease (AD) is derived from a set of 695-770 residue precursor proteins collectively referred to as the amyloid beta-protein precursor (beta APP). Using immunoblotting techniques, metabolic labeling, and sequencing we have analyzed beta APP derivatives in medium conditioned by: (1) human mononuclear leukemic (K562) cells expressing a model beta AP-bearing carboxyl-terminal beta APP derivati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 20 publications
0
29
0
Order By: Relevance
“…It has been clearly shown that transfection of human neuroblastoma with a /IAPP cDNA bearing the KM-NL double mutation leads to overproduction of A/I and A/I-bearing CT products (Citron et al, 1992;Cai et al, 1993;Golde et al, 1993;Felsenstein et al, 1994). However, lizuka et al (1991) reported that the KM-NL double mutation promoted the production of intracellular A/I and its release with no increase in level of CT fragment.…”
Section: Generation Of Amyloidogenic Ct Fragmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been clearly shown that transfection of human neuroblastoma with a /IAPP cDNA bearing the KM-NL double mutation leads to overproduction of A/I and A/I-bearing CT products (Citron et al, 1992;Cai et al, 1993;Golde et al, 1993;Felsenstein et al, 1994). However, lizuka et al (1991) reported that the KM-NL double mutation promoted the production of intracellular A/I and its release with no increase in level of CT fragment.…”
Section: Generation Of Amyloidogenic Ct Fragmentsmentioning
confidence: 99%
“…They suggested that amyloidogenic CT fragments can be produced by secretory cleavage of /IAPP, which is antegradely transported through axons in human brain. Recent work has shown that there is rapid processing of /IAPP in the optic nerve to generate a I 4-kDa terminal membrane-associated fragment that contains the A/I sequence (Amaratunga and Fine, 1995).CT 100 amyloidogenic fragments were produced by transgenic mice and rats with full-length human /IAPP containing native and genetic mutations linked to FAD and hereditary cerebral hemorrhage with amyloidosis of the Dutch type (Howland et al, 1995).It has been clearly shown that transfection of human neuroblastoma with a /IAPP cDNA bearing the KM-NL double mutation leads to overproduction of A/I and A/I-bearing CT products (Citron et al, 1992;Cai et al, 1993;Golde et al, 1993;Felsenstein et al, 1994). However, lizuka et al (1991) reported that the KM-NL double mutation promoted the production of intracellular A/I and its release with no increase in level of CT fragment.…”
mentioning
confidence: 99%
“…Because FSH receptors are primarily located in reproductive tissues, and others and we have not detected FSH receptors in neuronal cell types, we focused our efforts on biochemical changes modulated by LH. To test whether LH impacts A␤ generation we used the M17 neuroblastoma cell line (widely used for studying A␤PP processing (1,3,45,46)) to examine whether LH altered A␤PP expression and/or processing. Immunoblot analysis using polyclonal (Fig.…”
Section: Gonadotropin Lowering Hormone Decreases the Concentration Ofmentioning
confidence: 99%
“…A␤ is found in body fluids in a soluble form (16), which is partially ␣-helical (12,17). In Alzheimer's disease, A␤ undergoes conformational change and deposits in the extracellular space of the brain and in walls of cerebral blood vessels as amyloid plaques (1).…”
mentioning
confidence: 99%